TINDAKAN YURIDIS BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KABUPATEN TANAH DATAR DALAM MENINDAK PELANGGARAN PEMILIHAN UMUM PERSPEKTIF HUKUM TATA NEGARA ISLAM - Kintan Meiriza Awenza; Afdil Azizi (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
In writing this thesis, the focus of the study is how the role of the supervisory body of the Tanah Datar District Election Supervisory Agency in cracking down on violations of the money politics election, campaigning out of schedule, billboards and other campaign props that are widespread in the 2019 general election, what are the obstacles faced by the agency election supervisors in cracking down on violations of money politics elections, campaign props that were widespread at the time of the 2019 general election and the perspective of islamic constitutional law relating to the juridical actions of the election supervisory body against 2019 election violations.